Piezoelectric catalyst BaTiO3 and K0.5Na0.5NbO3 induced cellular and antibacterial response in poly (vinylidene fluoride) for self-powered implants for orthopedic applications - Kumar Das K.; Kesarwani U.; Prakash R.; Maiti P.; Shankar O.; Dubey A.K. (My University, 2025)
Despite of excellent biocompatibility of piezoelectric poly(vinylidene fluoride) (PVDF), lower resistance towards bacteria and piezoelectric coefficient restricts it's widespread application as self-powered implant. Towards this end, this study investigates the effect of incorporation of piezo-catalysts BaTiO3 (BT) and K0.5Na0.5NbO3 (KNN) into PVDF on piezo-catalytic characteristics, cellular and antibacterial response. Thin films of PVDF and its composites were prepared using the solvent casting method and hot compression molding. The piezo-catalytic response is observed to be notably higher in the composites than that of pure PVDF. The measured values of voltage, and power for PVDF, PVDF-10 wt% BT (PVDF-10BT) and PVDF-10 wt% KNN (PVDF-10KNN) are (24 V, ∼4.4 µW/cm2), (92 V, ∼15.8 µW/cm2) and (103 V, ∼19.4 µW/cm2), respectively. The presence of piezo-catalyst BT and KNN significantly enhance the cell proliferation, osteogenic differentiation (ALP) of MG-63 osteoblast-like cells and hemocompatibility. Incorporation of piezo-catalysts is observed to improve significantly the antibacterial response against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) due to a higher production of reactive oxygen species. These results suggest that PVDF modified with BaTiO3 and K0.5Na0.5NbO3 piezo-catalysts are promising candidates as self-powered implants for orthopedic applications. © 2025 Elsevier B.V.